Production of Survival: Cancer Politics and Feminist Media Literacies - Chelsey Hauge; Kate Reid (Studies in Social Justice, 2019)
In this paper, we argue that creative storytelling – by way of collaborative ethnographic songwriting and digital video production – can serve to complicate normative representations of breast cancer. We also argue that engaging in these artistic processes can be a practice of survival for people who do not see themselves in publicly available breast cancer narratives. At the center of our analysis is a song and music video, Breast Cancer Pink, which we composed and produced together about one author’s experience with young adult breast cancer. We make a case for media and feminist literacies, which we believe enabled the production of Breast Cancer Pink, for the author in question, who found herself on the margins of normative breast cancer narratives. We explore cultural dynamics around breast cancer, visual imaging, and creative practice and draw on Ahmed’s feminist notion of the feminist survival kit in order to understand typically invisible experiences of breast cancer.